Of men in mice: the success and promise of humanized mouse models for human malaria parasite infections. (6th March 2014) - Kaushansky, Alexis; Mikolajczak, Sebastian A.; Vignali, Marissa; Kappe, Stefan H. I.
Summary Forty percent of people worldwide are at risk of malaria infection, and despite control efforts it remains the most deadly parasitic disease. Unfortunately, rapid discovery and development of new interventions for malaria are hindered by the lack of small animal models that support the complex life cycles of the main parasite species infecting humans. Such tools must accommodate human parasite tropism for human tissue. Mouse models with human tissue developed to date have already enhanced our knowledge of human parasites, and are useful tools for assessing anti‐parasitic interventions. Although these systems are imperfect, their continued refinement will likely broaden their utility. Some of the malaria parasite's interactions with human hepatocytes and human erythrocytes can already be modelled with available humanized mouse systems. However, interactions with other relevant human tissues such as the skin and immune system, as well as most transitions between life cycle stages in vivo will require refinement of existing humanized mouse models. Here, we review the recent successes achieved in modelling human malaria parasite biology in humanized mice, and discuss how these models have potential to become a valuable part of the toolbox used for understanding the biology of, and development of interventions to, malaria.